Analysis of the Chinese Language Textbook: Easy Steps to Chinese 1 - Sugiarti, Tati; Rudiansyah, Rudiansyah; Lianisyah, Ulfah Yanuar; Adi, Dian Prasetyo; Avenida, Quinta (Makassar State University, 2025)
This study examines the Chinese language textbook Easy Steps to Chinese 1, which is used at SMP Kristen Shining Star Sragen. The focus is on evaluating the material in this textbook for its overall quality and effectiveness in supporting language learning. It aims to assess its suitability for junior high school learners, based on curriculum alignment and learner needs. A descriptive qualitative approach was used, including field observations, focus group discussions, and a review of relevant books, journals, and literature. In teaching Chinese, educators must be supported by textbooks that align with learners’ proficiency levels and learning objectives. Effective textbooks should incorporate relevant cultural and contextual elements to enhance both comprehension and practical language use. The results of this study led to the development of a compiled textbook, adapted from the original and aligned with the Kurikulum Merdeka and the school's vision and mission. This adapted textbook is intended to serve as a guide and reference for teachers in the Chinese language teaching and learning process at SMP Kristen Shining Star Sragen